THE CORRELATION BETWEEN THERAUPETIC COMMUNICATION AND THE ANXIETY OF PRE- OPERATED PATIENTS AT FLAMBOYAN WARD PUSRI HOSPITAL PALEMBANG 2016 - Tafdillah; Siti Revisia (STIK SITI KHADIJAH PALEMBANG, 2019)
Therapeutic communication and realtion which connected between nurse and patient could decrease the anxiety because the patient can explore their feeling, tell their anxiety to face the situation and got the solution. Based on the interview to 6 patients at Flamboyan ward Pusri Hospital Palembang, it was found that they feel anxious about painful after operation, physical change, and unsuccessful operation. The aim of this study was to find out the correlation between therapeutic communication and anxiety of pre-operated patient at Flamboyan ward Pusri hospital Palembang in 2016.This study was done from April 11-30 2016. The quantitative through cross sectional design was used in this study. The populastion of the study was all pre-operated patient at Flamboyan ward Pusri hospital Palembang. The accidental sampling technique was used to select the sample. The total number of the sample was 30 respondents. The univariate and bivariate analysis was used to analyze the data. The result of the study showed that there was a correlation between therapeutic communication and anxiety with -value 0,030 < 0,05. Finally, it is hoped that hospital stakeholders could conduct some trainings for therapeutic communication skill for the nurse to add their skill as one of standard operational before having an operation.